2021
DOI: 10.17582/journal.jahp/2021/9.3.271.276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera Leaf Powder as Feed Additives on Growth Performance and Blood Parameters of Broiler

Abstract: The current experiment was designed to investigate the impact of Moringa Leaf Powder as feed additives on growth performance and blood parameters of broilers. For this purpose, total of 240 DOC (Cobb-500) were purchased from the local market. On day of arrival at the farm, chicks were weighed and were divided equally into 4 experimental groups group A, group B, group C and group D having 3 replicas each containing 20 chicks in each replica. Standard feeding and managemental conditions were given to the chicks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Besarnya kandungan protein pada kelor membuat kelor menjadi pilihan yang ideal sebagai suplemen pada pakan ternak guna mendapatkan pakan ternak yang berkualitas. Mengingat potensi nutrisi dalam tanaman, dapat dianggap sebagai pengganti pakan tambahan (Khalid et al, 2021). Suplemen yang berasal dari Moringa oleifera telah dilaporkan dapat meningkatkan kinerja pertumbuhan dan 204 BRILIANT: Jurnal Riset dan Konseptual Volume 7 Nomor 1, Februari 2022 respon imun pada hewan ternak (Olugbemi et al, 2010).…”
unclassified
“…Besarnya kandungan protein pada kelor membuat kelor menjadi pilihan yang ideal sebagai suplemen pada pakan ternak guna mendapatkan pakan ternak yang berkualitas. Mengingat potensi nutrisi dalam tanaman, dapat dianggap sebagai pengganti pakan tambahan (Khalid et al, 2021). Suplemen yang berasal dari Moringa oleifera telah dilaporkan dapat meningkatkan kinerja pertumbuhan dan 204 BRILIANT: Jurnal Riset dan Konseptual Volume 7 Nomor 1, Februari 2022 respon imun pada hewan ternak (Olugbemi et al, 2010).…”
unclassified
“…The ability of MO to enhance growth traits, successfully prevent intestinal morphological atrophy, relieve oxidative damage, and downregulate mRNA expression of mucosal inflammatory genes in the jejunum under oxidative stress [ 12 ]. The findings indicate that there were notable variations in growth characteristics and feed costs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chick diet supplements with MO indicate greater performance (production) and immunity than untreated chicks [ 11 ]. The dietary leaf powder of MO might enhance physiological and physiochemical features as well as intestinal health in birds, which is linked to the Moringa leaf’s capacity to reduce inflammation in the intestinal tract [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-origin contains active compounds that have biological activities, especially antibacterial, anti-inflammatory, antioxidant, and immune-modulatory properties which are known to be helpful for the animal's health and enhance productivity (Windisch et al, 2008;Hashemi and Davoodi, 2010). Some previous studies showed that administration of phytobiotics feed additives improved the growth rate and feed efficiency (Abu-Dieyeh and Abu-Darwish, 2008;Oso et al, 2019;Ampode and Asimpen, 2021;Khalid et al, 2021) in broiler chickens. Administration of phytobiotic additives has also been reported to affect hematological parameters in broiler chickens (Ansari et al, 2012;Basit et al, 2020), which is a good indicator in evaluating the physiological and health status of animals.…”
Section: Introductionmentioning
confidence: 99%